Systematic review of the coach-athlete relationship from the coaches´ perspective - McShan; K.; Moore, W. G. (Kinesiology Review, 2023)
The purpose of this study was to systematically review the variables associated with the coach-athlete relationship (CAR) from the coaches` perspective. Three databases were searched; 57 studies published between January 2000 and May 2021 met the inclusion criteria. Correlates (n = 35) were grouped into three categories: coach variables, athlete variables, and coaching behaviors. Variables positively associated with the coaches` perspective of the CAR included coaching satisfaction, the teaching of life skills, and engaging in need-supportive behaviors. Negative correlates included coaching burnout, athletes` avoidant attachment style, and coaches` controlling behaviors. Aside from coach satisfaction, many of the relationships mentioned came from only one or two studies; therefore, replication studies are needed examining CAR from the coaches` perspective. In conclusion, the better coaches report CAR to be, the more they also report fostering a caring and autonomy-supportive environment, teaching life skills, and being satisfied with their coaching experience.